Evaluation of durum wheat varieties for yield and yield related traits in highland areas of southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2021)
Durum wheat productivity in Ethiopia is hindered by different factors mainly lack of improved adapted varieties for specific locations. This experiment was done to identify the most performing durum wheat varieties in the tested environment. The average productivity of the tested genotypes were evaluated at two locations (Alicho and Analimo) using randomized complete block design with four replication for two consecutive years (2016 and 2017). The experimental material consists of seven improved durum wheat genotypes. The Combined analysis of variance showed significant (P